Biomass preservation in impact melt ejecta - Howard, K.; Bailey, M.; Berhanu, D.; Bland, Phil; Cressey, G.; Howard, L.; Jeynes, C.; Matthewman, R.; Martins, Z.; Sephton, M.; Stolojand, V.; Verchovsky, S. (Nature Publishing Group, Macmillan Publishers Ltd, 2013)
Meteorites can have played a role in the delivery of the building blocks of life to Earth only if organic compounds are able to survive the high pressures and temperatures of an impact event. Although experimental impact studies have reported the survival of organic compounds1–6, there are uncertainties in scaling experimental conditions to those of a meteorite impact on Earth1–6 and organic matter has not been found in highly shocked impact materials in a natural setting. Impact glass linked to the 1.2-km-diameter Darwin crater in western Tasmania7–9 is strewn over an area exceeding 400 km2 and is thought to have been ejected by a meteorite impact about 800 kyr ago into terrain consisting of rainforest and swamp7,10. Here we use pyrolysis–gas chromatography–mass spectrometry to show that biomarkers representative of plant species in the local ecosystem—including cellulose, lignin, aliphatic biopolymer and protein remnants—survived the Darwin impact. We find that inside the impact glass the organic components are trapped in porous carbon spheres. We propose that the organic material was captured within impact melt and preserved when the melt quenched to glass, preventing organic decomposition since the impact. We suggest that organic material can survive capture and transport in products of extreme impact processing, at least for a Darwin-sized impact event.